MINAT KUNJUNGAN WISATAWAN TERHADAP GUWANG BARONG DAN KERIS DANCE : ANALISIS PERAN ATRAKSI, AMENITAS DAN KEUNIKAN BUDAYA - Anak Agung Istri Agung Maheswari; Komang Nila; Nyoman Sri Manik Parasari; I Putu Dharmawan Pradhana (Bajang Institute, 2025)
Problem: The number of tourists visiting Guwang Barong and Keris Dance is still below ideal. This is ascribed to the dearth of distinctive tourist attractions, the small selection of attractions, and the subpar infrastructure that prevents guests from having a positive experience. The purpose of this research is to ascertain how tourism attractions, amenities, and attractions affect travelers' desire to see Guwang Barong and Keris Dance. Method: Partial Least Squares (PLS) analysis is the data analysis technique used. Results: According to the research, tourism attractions, amenities, and attractions all significantly and favorably affect travelers' desire to see Guwang Barong and Keris Dance. According to the research, tourist attractions had a 34.5% positive influence on visitors' attention, with a p-value of 0.000 and a t-statistic value of 3.497. Additionally, a t-statistic value of 2.822 and a p-value of 0.005 corroborate the 25.7% positive influence of attractions on visit interest. Additionally, with a t- statistic value of 2.847 and a p-value of 0.004, sufficient facilities are linked to a 29.9% rise in visit interest. These results demonstrate that visitors' interest in visiting Guwang Barong and Keris Dance is greatly increased by distinctive tourist attractions, interesting activities, and well-equipped facilities